Application of the Protoplast Fusion Technique to Engineer a Recombinant Microorganism to More Efficiently Degrade Chlorophenols - Honglei Chen; Yu Liu; Fangong Kong; Lucian A. Lucia; Xiaojing Feng (BioResources, 2015)
Recombinant strain Xz6-1 was constructed by the protoplast fusion technique with the goal of endowing it with the ability to efficiently degrade pentachlorophenol (PCP). This compound was considered as a representative of possible compounds that can be obtained during the bleaching of pulp for papermaking. The potential of Xz6-1 and Pseudomonas putida to treat PCP synthetic wastewater was explored. The majority of PCP was removed within the first 20 h; two degradation curves were obtained that followed first-order reaction kinetics. The kinetics data revealed that the rate constant for degradation of PCP for Xz6-1 was 0.063 h-1, a value that was over 50% greater than that of Pseudomonas putida (0.040 h-1). Aerobic granular sludge was highly fortified with Xz6-1 and Pseudomonas putida to provide PCP degradability improvements of 180.9% and 98.3%, respectively, relative to the original sludge. All results demonstrate that the protoplast fusion technique is an effective approach to construct a high-activity chlorophenol-degrading strain.